Gender in the ancient Near East - Budin, Stephanie Lynn, author.
1 online resource (xiv, 309 pages)
Keywords: "Gender in the Ancient Near East is a wide-ranging study through text and art that presents our current understanding of gender constructs in ancient Mesopotamia, Egypt, Anatolia, Cyprus, and the Levant and incorporates current trends in gender theory. Budin begins with definitions of sex and gender in modern society and scholarship before exploring ancient Near Eastern understandings of these concepts. Readers are then guided through sources in translation in order to understand how the denizens of the ancient Near East understood notions of femininity, masculinity, and other, with a final chapter considering how modern notions of hetero- and homosexuality apply to the ancient world. The volume also explores how these concepts are portrayed in ancient art and material culture through accompanying photographs and illustrations. The overview of both Near Eastern history and contemporary gender theory allows readers unfamiliar with the material easily to approach the subject and draw meaningful conclusions. Gender in the Ancient Near East offers a comprehensive and engaging introduction to the subject for students of the Ancient Near East and of gender in the ancient world. It is also of interest to those working in Gender Studies and Queer Studies"--